2019
DOI: 10.2174/1871529x19666190410145501
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Dispersion and Silent Atrial Fibrillation in Cryptogenic Stroke: The Pathogenic Role of Inflammation

Abstract: Background: Cryptogenic stroke (CS) represents 25% of ischemic strokes. Especially after CS, the detection of atrial fibrillation (AF) is important because it provides clues to the mechanism of stroke. However, the relationship between AF and stroke appears more complex than a simple cause-effect mechanism, suggesting that the association between AF and stroke may be due to other systemic and atrial factors including systemic inflammation that may lead to atrial remodeling and subsequent atrial cardiopathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Some findings on the ECG can point to the risks of developing this clinical condition, though the information is difficult to detect. P‐wave‐related parameters provide clinicians with very useful information about AF 16,17 . Among these parameters, PWPT has gained an important place in predicting AF, especially in recent years 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Some findings on the ECG can point to the risks of developing this clinical condition, though the information is difficult to detect. P‐wave‐related parameters provide clinicians with very useful information about AF 16,17 . Among these parameters, PWPT has gained an important place in predicting AF, especially in recent years 18,19 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 23 A study of stroke patients with new onset or episodes of paroxysmal AF has shown that increased serum inflammatory markers was associated with prolonged PWD and thus supporting the role of inflammation in developing AF. 24 Another important factor is the role of testosterone in BPH disease as studies have shown that low levels of serum testosterone are directly related to the development and the progress of prostatic hyperplasia aggravating lower urinary tract symptoms. 8 , 23 On the other hand, the FINRISK97 study showed that low testosterone levels have a predictive value for future atrial fibrillation development in men.…”
Section: Discussionmentioning
confidence: 99%
“…Hs‐CRP is a classic risk factor for inflammation associated with atherosclerosis, and the hs‐CRP levels are known to be significantly higher in patients who had an ischemic stroke than in controls. Acampa reported that hs‐CRP levels were associated with atrial fibrillation development in patients with cryptogenic stroke, and hs‐CRP may be a potential therapeutic target for preventing atrial fibrillation in patients with cryptogenic stroke. However, in this study, no significant difference was noted between ischemic stroke patients with H‐type hypertension and those with non‐H‐type hypertension.…”
Section: Discussionmentioning
confidence: 99%